The Edinburgh companion to the Bible and the arts - Prickett, Stephen (Edinburgh University Press, 2014)
Examines the changing relationship between the Bible and the arts, showing how the arts portray biblical stories in various ways and through various media, and how 'the' Bible is actually multiple entities: fiercely contested translations in many languages. Generously illustrated with examples including painting, architecture and stained glass.
Keywords: Bibeln.; Bibel; Arts in the Bible.; Christian art and symbolism.; Arts dans la Bible.; LITERARY CRITICISM / Reference; Arts in the Bible; Christian art and symbolism; Architektur; Kunst; Künste; Literatur; Rezeption; Ästhetik; Historiska händelser i Bibeln.; Kristen konst och symbolik.; Bibliska motiv i litteraturen.; Bibliska motiv i konsten.; Estetik -- religiösa aspekter.; Religion.; Electronic book.